The English students' anxiety in speaking - Merri Sri Hartati; Wahyudi Badri; Indra Nur Rhomadon; Tri Rahayu Setya Ningrum; Isni Dwi Rahma; Rianti Rahmadania (Journal of English Language and Pedagogy, 2025)
This study aims to investigate the types of speaking anxiety experienced by English students and to identify the most dominant type of anxiety among them. The subjects were 20 fourth-semester students of the English Study Program at Universitas Muhammadiyah Bengkulu during the 2024/2025 academic year. A descriptive qualitative method was employed, utilizing questionnaires and interviews for data collection. The findings revealed that students experienced three main types of anxiety: communication apprehension, test anxiety, and fear of negative evaluation. Among these, fear of negative evaluation emerged as the most dominant. The study highlights the need for supportive learning environments that reduce anxiety and enhance students’ confidence in speaking English.